2020
DOI: 10.1186/s13073-020-00730-9
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric cohesion failure invokes a conserved choreography of chromosomal mis-segregations in pancreatic neuroendocrine tumor

Abstract: Background: Pancreatic neuroendocrine tumors (PANETs) are rare, slow growing cancers that often present with local and distant metastasis upon detection. PANETS contain distinct karyotypes, epigenetic dysregulation, and recurrent mutations in MEN1, ATRX, and DAXX (MAD+); however, the molecular basis of disease progression remains uncharacterized. Methods: We evaluated associations between aneuploidy and the MAD+ mutational state of 532 PANETs from 11 published genomic studies and 19 new cases using a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Accordingly, mislocalization of CENP-A resulting from its overexpression contributes to chromosomal instability and aneuploidy ( Shrestha et al, 2021 ), which have long been recognized as hallmarks of tumor growth, malignant progression, and treatment resistance ( Zhang et al, 2016 ; Sansregret et al, 2018 ). Recent studies have indicated that CENP-A overexpression induces chromosomal instability in cancer cells ( Amato et al, 2009 ; Quevedo et al, 2020 ). Additionally, increased CENP-A expression is implicated in malignant progression ( Sun et al, 2016 ) and correlates with poor prognosis in cancers ( Zhang et al, 2020a ; Saha et al, 2020 ; Xu et al, 2020 ), including breast ( Rajput et al, 2011 ), lung ( Wu et al, 2012 ; Liu et al, 2018 ), and hepatic carcinoma ( Zhang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, mislocalization of CENP-A resulting from its overexpression contributes to chromosomal instability and aneuploidy ( Shrestha et al, 2021 ), which have long been recognized as hallmarks of tumor growth, malignant progression, and treatment resistance ( Zhang et al, 2016 ; Sansregret et al, 2018 ). Recent studies have indicated that CENP-A overexpression induces chromosomal instability in cancer cells ( Amato et al, 2009 ; Quevedo et al, 2020 ). Additionally, increased CENP-A expression is implicated in malignant progression ( Sun et al, 2016 ) and correlates with poor prognosis in cancers ( Zhang et al, 2020a ; Saha et al, 2020 ; Xu et al, 2020 ), including breast ( Rajput et al, 2011 ), lung ( Wu et al, 2012 ; Liu et al, 2018 ), and hepatic carcinoma ( Zhang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The index paper we reference (Lawrence and colleagues) used the terms “recurrent 10 chromosome monosomy” and “10 chromosome loss of heterozygosity (LOH)” which are more accurate; however, other authors have referenced the loss of a slightly different number of chromosomes. For example, Quevedo et al13 referenced a “signature of loss of heterozygosity and copy-number alterations affecting 11 chromosomes.” Importantly, mentioning only the lost chromosomes excludes which chromosomes must be preserved, thus a case with global loss of heterozygosity could inappropriately fall into this category. In addition, many authors referenced the signature predominantly as a relative gain or absolute gain of the nonlost chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…12 This simple biologic mechanism to explain recurrent chromosomal losses has come into question recently. 13 Quevedo and colleagues found the 11-chromosome loss of heterozygosity signature (losses of chromosomes 1, 2, 3, 6, 8, 10, 11, 15, 16, 21, and 22), associated with mutations of MEN1, DAXX and/or ATRX, is likely the result of centromeric cohesion failure and mis-segregation, not necessarily ALT as previously described. Although they found indications that an ALT phenotype existed in these DAXX/ATRX/MEN1 mutant tumors, they postulate that the disruption of H3.3 deposition at genomic repeats, found both at telomeres and centromeres, could be the potential mechanism of genomic instability.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Centromere, which contains a special nucleosome CENP-A histone, provides not only the basis for centromere chromatin and kinetochore assembly but also a locus for kinetochore-microtubule attachment and spindle assembly checkpoints. Recent studies have emphatically pointed out that ectopic localization of CENP-A induces kinetochore defects and the chromosomal instability phenotype in many cancers [ 46 , 47 ]. Previously, Obuse C et al identified that RSF1 and SNF2H co-exist in CENP-A affinity eluates using chromatin immunoprecipitation (ChIP) and mass spectrometric analysis in HeLa cells [ 48 ].…”
Section: Rsf1 Recruits Cenp-a To Centromeres To Maintain Accurate Chromosome Segregationmentioning
confidence: 99%